Performance as Philosophy — the universal language of the theatre revisited - Meyer-Dinkgräfe, Daniel; Hammer, Anita S. (Nordic Theatre Studies, 2017)
The history of philosophy is widely considered as the history of exercises in speculation. However, it is also possible to understand philosophy not as the outcome of speculation, but at the attempt by philosophers to explain, make sense of, and ultimately share, their own experiences of a very subtle, powerful and spiritual nature. The growing field of performance philosophy begins to acknowledge the potential of considering philosophy as an expression of immediate experience rather than distant speculation. This acknowledgement can take the shape of employing performance to express philosophy — in more immediately experienced ways than verbal language is ever able to convey. Writing about this non-verbal dimension is difficult, and the result limited by its very nature, but in this article, we discuss the principle, and provide an example in the performance philosophy, captured under the term of body thinking, of German philosopher and dancer Aurelia Baumgartner.